Qumran Studies: New Approaches, New Questions. By Michael Thomas Davis and Brent A. Strawn. With a Foreword by James E. Sanders - Hempel, Charlotte (The journal of theological studies, 2011)
This collection of eleven papers is dedicated to Prof. James H. Charlesworth by students and collaborators on the Princeton Theological Seminary Dead Sea Scrolls Project. J. B. Faulkenberry Miller’s chapter on 4QLXXLeva joins a fast-moving discussion suffering somewhat from the rapid pace of scholarship that appeared between the oral presentation of the papers in 2001 and the publication of the volume in 2007. H. W. Morisada Rietz revisits the issue of the relationship of the Songs of the Sabbath Sacrifice to the Qumran community, suggesting dependence on a passage in the Treatise of the Two Spirits (1QS 3:15 f.). The possible pre-existence of the Treatise suggested by 4QSd, an ancient manuscript of the Rule that circulated without it, is a vital part of the argument not developed here.